2020
DOI: 10.1186/s13717-020-00225-w
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation and ecosystem carbon recovery following shifting cultivation in Mizoram-Manipur-Kachin rainforest eco-region, Southern Asia

Abstract: Background Shifting cultivation (locally known as “jhum”) is a major driver of deforestation and loss of ecosystem services in rainforests. For developing any effective conservation of biodiversity and carbon service program, an in-depth understanding to the recovery of vegetation and carbon after abandonment of jhum is essential. We estimated species richness, abundance and composition of trees, shrubs and herbs, carbon distribution in aboveground and belowground components along a chronoseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 54 publications
5
12
1
Order By: Relevance
“…Saplings and seedlings diversity and evenness index also followed a similar pattern. However, these results from the communities fall within the ranges of (2.00 to 4.86) and (0.21 to 1.00) reported in tropical forests in Ghana [20], [21], [22] and elsewhere [15], [17], [23]. These results showed that each community is very diverse, stable and well adapted [17], [23].…”
Section: B Species Diversity In the Togo Plateau Forest Reservesupporting
confidence: 82%
See 4 more Smart Citations
“…Saplings and seedlings diversity and evenness index also followed a similar pattern. However, these results from the communities fall within the ranges of (2.00 to 4.86) and (0.21 to 1.00) reported in tropical forests in Ghana [20], [21], [22] and elsewhere [15], [17], [23]. These results showed that each community is very diverse, stable and well adapted [17], [23].…”
Section: B Species Diversity In the Togo Plateau Forest Reservesupporting
confidence: 82%
“…However, these results from the communities fall within the ranges of (2.00 to 4.86) and (0.21 to 1.00) reported in tropical forests in Ghana [20], [21], [22] and elsewhere [15], [17], [23]. These results showed that each community is very diverse, stable and well adapted [17], [23]. Probable causes for the local variations in species composition and structure among the communities include the geographical locations of these communities which somehow correspond with different elevations to the plateau (i.e., BO, NK occur in lower and gentle elevations, AK, SA in mid elevation and HH, AL in higher elevations with rocky and varied inclined slope areas).…”
Section: B Species Diversity In the Togo Plateau Forest Reservesupporting
confidence: 79%
See 3 more Smart Citations